Human-Nature Interactions Exploring Nature's Values Across Landscapes - Misiune, Ieva; Depellegrin, Daniel; Egarter Vigl, Lukas (Springer Nature, 2022)
This edited volume aims to widen the discussion about the diversity of human-nature relationships and valuation methods and to stimulate new perspective that are needed to build a more sustainable future, especially in face of ongoing socio-environmental changes. Conceptual and empirical approaches, including qualitative, quantitative, and mixed methodologies have been used to highlight the importance of an integrative understanding of socio-ecological systems, where healthy ecosystems underpin the quality of life and societal activities largely drive environmental changes. Readers will obtain a comprehensive overview of the many and diverse ways the relationships between people and nature can be characterized. This includes understanding how people assign values to nature, discuss how human-nature interactions are shaped and provide examples of how these values and interactions can be systematically assessed across different land systems in Europe and beyond. This open access book is produced by internationally recognized scientists in the field but written in an accessible format to be of interest to a large audience, including prospective students, lecturers, young professionals and scientists embarking to the interdisciplinary field of socio-ecological research and environmental valuation.